Pigtail assisted tracking of guide catheter for navigating the difficult radial: Overcoming the “razor effect” - Naveen Garg (Indian Heart Journal, 2016)
During transradial procedures, sharp edge of the guide catheter tip may act like a “razor-blade” and can prevent the catheter navigation. It is especially common with radial artery loop, tortuous radial artery and radial artery spasm. We describe a cost effective and easy technique which overcomes this “razor-blade” effect and helps in tracking the guide catheter in complex radial anatomy for the easy and successful completion of procedure.